2020
DOI: 10.3390/tropicalmed5030147
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Induced Thrombosis in Patients without Gastrointestinal Symptoms and Elevated Fecal Calprotectin: Hypothesis Regarding Mechanism of Intestinal Damage Associated with COVID-19

Abstract: Background: Patients with coronavirus infectious disease 2019 (COVID-19) and gastrointestinal symptoms showed increased values of fecal calprotectin (FC). Additionally, bowel abnormalities were a common finding during abdominal imaging of individuals with COVID-19 despite being asymptomatic. The current pilot study aims at evaluating FC concentrations in patients without gastrointestinal symptoms. Methods: we enrolled 25 consecutive inpatients with COVID-19 pneumonia, who were admitted without gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 15 publications
1
31
1
1
Order By: Relevance
“…The consistent presence of granulocytes, as reported by the two authors [ 11 , 12 ], may be crucial in understanding the mechanism behind the increase in FC of our patient, given that FC is mainly expressed in neutrophils. Apart from this patient, whose clinical condition deteriorated rapidly, an increase in FC was reported recently in patients without gastrointestinal symptoms or previous history of inflammatory disease [ 9 ]. According to these preliminary findings, FC should be assessed in COVID-19 patients on admission, and abdominal imaging might be performed in cases of elevated FC even without gastrointestinal symptoms.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The consistent presence of granulocytes, as reported by the two authors [ 11 , 12 ], may be crucial in understanding the mechanism behind the increase in FC of our patient, given that FC is mainly expressed in neutrophils. Apart from this patient, whose clinical condition deteriorated rapidly, an increase in FC was reported recently in patients without gastrointestinal symptoms or previous history of inflammatory disease [ 9 ]. According to these preliminary findings, FC should be assessed in COVID-19 patients on admission, and abdominal imaging might be performed in cases of elevated FC even without gastrointestinal symptoms.…”
Section: Discussionmentioning
confidence: 77%
“…In particular, gastrointestinal symptoms appear to affect 28% of patients with COVID-19 [ 4 ], with increasing rates of presentation according to the severity of the disease [ 5 ]. Additional findings include the detection of fecal viral RNA in around 50% of patients [ 6 , 7 , 8 ], the measurement of increased fecal calprotectin (FC) in patients, with or without gastrointestinal symptoms [ 9 , 10 ], and the detection of bowel wall abnormalities in 31% of computed tomography (CT) performed on patients with COVID-19 [ 11 ]. In a few cases, the abdominal involvement of COVID-19 resulted in spontaneous bowel perforation [ 9 , 11 , 12 , 13 ], and, to the best of our knowledge, no rectal perforation has ever been described before.…”
Section: Introductionmentioning
confidence: 99%
“…We propose these ratios should be incorporated with other epidemiological and clinical variables in a nomogram to help identify moderate to severe cases of COVID-19, given their capacity to signal a combination of hyperinflammatory response and microvascular occlusion that has been identified in the pathophysiology of moderate to severe cases [ 12 , 13 ]. Early detection of patients affected by COVID-19 who will have worse evolution is a priority.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported significantly elevated levels of calprotectin in patients with severe COVID-19 and the possible ability of calprotectin to discriminate between mild and severe form of the disease 3 , 4 , 5 . In addition, elevated fecal calprotectin has been shown to associate with thromboembolic events in COVID-19 in the absence of gastrointestinal manifestations 6 . However, it is not yet fully elucidated whether changes of calprotectin serum levels occur prior to the progression to severe disease and therefore might be detectable already at an early stage of COVID-19, e.g.…”
mentioning
confidence: 99%